2013
DOI: 10.1002/hyp.9681
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent catchments with similar patterns of land use and climate have markedly different dissolved organic carbon concentration and runoff dynamics

Abstract: Temporal patterns in specific runoff, dissolved organic carbon concentrations [DOC] and fluxes were examined during two periods: 1994–1997 (period 1) and 2007–2009 (period 2) in five adjacent tributary catchments of Lake Simcoe, the largest lake in southern Ontario, Canada. The catchments displayed similar patterns of land use change with increases in urbanization (5–16%) and forest cover (0.2–4%) and declines in agriculture (4–8%) between 1994 and 2008. Climate in the catchments was similar; temperature incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 49 publications
0
23
0
5
Order By: Relevance
“…Previous remote sensing analysis, as presented in Oni et al . (), showed that land use change was evident across the LSW. The results showed that impervious surfaces increased by 5–16% because of urbanization, forest slightly increased by 4%, while agriculture declined by 4–8% across the LSW.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous remote sensing analysis, as presented in Oni et al . (), showed that land use change was evident across the LSW. The results showed that impervious surfaces increased by 5–16% because of urbanization, forest slightly increased by 4%, while agriculture declined by 4–8% across the LSW.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research in the LSW (Oni et al ., ) showed significant site‐by‐period interactions for run‐off across the watershed. Landscape development such as urbanization could amplify catchment run‐off flashiness during spring melt regimes (Cheng and Wang, ) and enhance overland flow that results in greater run‐off peaks (Rose and Peters, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is a great deal of research interest in Prediction in Ungauged Basins (PUB; Hrachowitz et al, 2013a, and references therein), PERSiST has been designed for use in flow simulations at gauged catchments. Thus, regionalization studies such as Hellebrand et al (2011) have very different modelling goals than those motivating the development of PERSiST, which may be more useful for understanding the differences in hydrological response between apparently similar catchments such as those reported by Oni et al (2013).…”
Section: Persist and Other Modelsmentioning
confidence: 99%
“…This has been described as "Aqua Incognita" by Bishop et al (2008). Large river basins will contain a mixture of DOC of different quality from various landscape sources making the DOC dynamics more uniform over time and space (Oni et al, 2013). In contrast, the DOC processes in headwaters are dependent on both local soil conditions and hydrology that both have a heterogeneous nature.…”
Section: Introductionmentioning
confidence: 99%